2014
DOI: 10.1158/0008-5472.can-14-1084
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Thiol Expression Increases the Durability of Antitumor T-cell Functions

Abstract: Ex vivo-expanded CD8+ T cells used for adoptive immunotherapy generally acquire an effector memory-like phenotype (TEM cells). With regard to therapeutic applications, two undesired features of this phenotype in vivo are limited persistence and reduced anti-tumor efficacy, relative to CD8+ T cells with a central memory-like phenotype (TCM cells). Further, there is incomplete knowledge about all the differences between TEM and TCM cells that may influence tumor treatment outcomes. Given that TCM cells survive r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…The expression of cyclin dependent kinase inhibitors CDKn1a , CDKn2a , and CDKn2b , which are regulated by p53 were also significantly reduced in h3T- p53 KO cells as compared to h3T T cells (Figure 1C). In addition, higher proliferation rate could lead the T cells close to replicative senescence with increased CD62L lo phenotype and susceptibility to cell death (3). A recent study has also shown p53 isoform switching regulates tumor associated replicative senescence T cells (17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of cyclin dependent kinase inhibitors CDKn1a , CDKn2a , and CDKn2b , which are regulated by p53 were also significantly reduced in h3T- p53 KO cells as compared to h3T T cells (Figure 1C). In addition, higher proliferation rate could lead the T cells close to replicative senescence with increased CD62L lo phenotype and susceptibility to cell death (3). A recent study has also shown p53 isoform switching regulates tumor associated replicative senescence T cells (17).…”
Section: Resultsmentioning
confidence: 99%
“…Since Tcm phenotype is associated with higher anti-oxidant capacity and reduced cell death (3), we determined ROS/RNS levels and AICD levels between h3T- p53 KO vs. h3T T cells. Upon TCR restimulation with cognate tyrosinase antigen h3T- p53 KO T cells secreted less ROS (measured using DCFDA dye), and RNS (measured using DAF dye), as compared to h3T T cells (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 This agrees with studies showing that IL-15-activated human NK cells are functionally resistant to steroid inhibition 37 and sustain their superior in vivo proliferation. 1,35,38 In T cells, IL-15 promotes survival via upregulating Bcl-2 39,40 and antioxidant proteins 41,42 and limiting proapoptotic caspase-3. 43 In addition, we show that the expression of activating NK-cell receptors is upregulated on IL-2-expanded NK cells after short-term incubation with IL-15, possibly contributing to the result that, upon injection into immunodeficient mice, the frequency of IL-15-expanded NK cells in the liver was higher as compared with IL-2-expanded NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…2 Our study highlights that using Rapamycin -a drug that is known to enhance CD62L expression, 3 also increases anti-oxidant capacity of the T cells. It is likely that in addition to its role as mTOR inhibitor and regulating metabolic commitment of a T cell, rapamycin pre-treated T cells persist better in a tumor microenvironment and exhibit improved anti-tumor function because increased capacity to resist oxidative stress.…”
mentioning
confidence: 77%